1982
DOI: 10.3382/ps.0611897
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Growing Turkey Hens as Influenced by Supplemental Dietary Fat and Different ME:Nutrient Ratios

Abstract: Rate of gain and feed efficiency of growing hen turkeys from 1 to 126 days of age was improved by supplementing diets with a blended fat at levels ranging from 2 to 8%. The favorable response to supplemental fat occurred with diets base on corn or milo with the greatest responses obtained with the corn-based diets. There was no significant difference in body weight and feed efficiency between the hens receiving diets in which the concentration of nutrients were adjusted with increases in metabolizable energy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Many studies have shown that the dietary addition of fats or vegetable oils improves the performance of broilers (Vemeersch and Vanschoubroek, 1968;Fuller and Rendon, 1977;Griffith et al, 1977) wards and Morris, 1976;Sell et al, 1976;Jensen, 1983;Reid, 1985), and turkeys (Salmon and O'Neill, 1971;Potter et al, 1974;Kagan, 1981;Owings and Sell, 1982). It has also been shown that dietary fat is a more efficient source of energy than dietary carbohydrate or protein (Donato and Hegsted, 1985).…”
Section: Introductionmentioning
confidence: 93%
“…Many studies have shown that the dietary addition of fats or vegetable oils improves the performance of broilers (Vemeersch and Vanschoubroek, 1968;Fuller and Rendon, 1977;Griffith et al, 1977) wards and Morris, 1976;Sell et al, 1976;Jensen, 1983;Reid, 1985), and turkeys (Salmon and O'Neill, 1971;Potter et al, 1974;Kagan, 1981;Owings and Sell, 1982). It has also been shown that dietary fat is a more efficient source of energy than dietary carbohydrate or protein (Donato and Hegsted, 1985).…”
Section: Introductionmentioning
confidence: 93%
“…Growth response to fat diminishes as its dietary level increases. Owen et al (1981) noted that male turkeys showed no further improvement in rate of gain beyond 40 g added fat/kg in maize-soya-bean-meal rations; however, Owings & Sell (1982) found female turkeys to benefit from up to 80 g added fat/kg under similar dietary circumstances. Differences in the maximum level for response probably relates to the proportion of growth devoted to fat and the amount needed from the feed to offset the limitation in de tuyuo synthesis.…”
Section: Growth Response To Fatmentioning
confidence: 99%
“…Data presented by Jensen et al (1970) and Waibel (1978) showed that when various combinations of protein and ME concentrations were fed, significant main effects of protein and ME were observed, but that no protein X ME level interaction occurred. Sell and Owings (1981) and Owings and Sell (1982) found that increasing the ME, by using supplemental fat, improved performance of toms and hens, respectively, whether the concentrations of key nutrients remained constant or were increased commensurate with changes in ME level.…”
Section: Introductionmentioning
confidence: 93%